Effect of alcoholic extract of black seed, red tea and tannins of oak tannins on the vitality of the primary heads Echinococcus granulosus of the granule thorns of sheep origin in glass - Ibraheem Abdullah; Foad Ismail (College of Education for Pure Sciences, 2007)
The results of this study revealed significant effect of an alcoholic extracts of the seeds of Nigella sativa L. , calyx of the red tea Hibiscus sabdariffa L. and nutgalls of Quercus infectora Oliv. in concentrations of 2.5 mg/ml 5 mg/ml, 7.5 mg/ml and 10 mg/ml for the seeds of Nsativa, and the concentrations of 50mg/ml, 75mg/ml, 100mg/ml and 150mg/ml for the calyx of the red tea , H. sabdariffa and concentrations 5mg/ml , 7 .5mg/ml , 1 Omg/ml and 15mg/ml for the nutgalls of Q. infectoria on the viability of the protoscoleces of Echinococcus granulosus of sheep origin in vitro.